Emmanuel Joseph Sieyès: The Essential Political Writings - Lembcke, Oliver W.; Weber, Florian (Studies in the History of Political Thought, 2014)
The edition contains all of Sieyès's "Essential Political Writings" during the revolutionary decade (1789-1799), among them his famous pamphlet What is the Third Estate? as well as the less well known, but no less important later Thermidor speeches.